The biology and mathematical modelling of glioma invasion: a review - Alfonso, Juan Carlos Lopéz; Talkenberger, K.; Seifert, M.; Klink, Barbara; Hawkins-Daarud, A.; Swanson, K. R.; Hatzikirou, H.; Deutsch, A. (Interface, 2017)
Adult gliomas are aggressive brain tumours associated with low patient survival rates and limited life expectancy. The most important hallmark of this type of tumour is its invasive behaviour, characterized by a markedly phenotypic plasticity, infiltrative tumour morphologies and the ability of malignant progression from low- to high-grade tumour types. Indeed, the widespread infiltration of healthy brain tissue by glioma cells is largely responsible for poor prognosis and the difficulty of finding curative therapies. Meanwhile, mathematical models have been established to analyse potential mechanisms of glioma invasion. In this review, we start with a brief introduction to current biological knowledge about glioma invasion, and then critically review and highlight future challenges for mathematical models of glioma invasion.